2012
DOI: 10.1111/j.1095-8649.2012.03359.x
|View full text |Cite
|
Sign up to set email alerts
|

Dining hall at sea: feeding migrations of nektonic predators to the eastern Patagonian Shelf

Abstract: Seasonal changes in relative abundance and biomass of nektonic predators were analysed on the eastern Patagonian Shelf and continental slope; one of the most productive large marine ecosystems of the southern hemisphere. Several migratory types were revealed for species belonging to either temperate or sub‐Antarctic faunas. Despite high productivity, only a few large nektonic predators spend their entire life cycle on the eastern Patagonian Shelf and use only a small proportion of the meso‐nektonic resource. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…All four of the predominant species are relatively large‐sized within the Falkland Islands skate assemblage (Arkhipkin et al , 2012 a ), suggesting that large skate species in the same environment can respond differently to the same fishing pressures. Results of this study contrast with Agnew et al 's () prediction that B. albomaculata and B. brachyurops should sustain higher fishing pressures than B. griseocauda and Z. chilensis , which Agnew et al () found to have higher age at maturity.…”
Section: Discussionmentioning
confidence: 99%
“…All four of the predominant species are relatively large‐sized within the Falkland Islands skate assemblage (Arkhipkin et al , 2012 a ), suggesting that large skate species in the same environment can respond differently to the same fishing pressures. Results of this study contrast with Agnew et al 's () prediction that B. albomaculata and B. brachyurops should sustain higher fishing pressures than B. griseocauda and Z. chilensis , which Agnew et al () found to have higher age at maturity.…”
Section: Discussionmentioning
confidence: 99%
“…On the Falkland Islands Shelf, two marine ecosystems, the southern temperate ecosystem and the sub‐Antarctic ecosystem, are separated by an ecotone running from the south‐west to the north‐east of the Patagonian Shelf through the Falkland Islands archipelago. This situation is essentially created by the varying strengths of the two Falkland Islands currents (east and west) and the influence of the Argentine Drift to the west . A number of oceanographic fronts exist on the Falkland Islands shelf itself, mainly in areas to the south and east of the Falkland Islands.…”
Section: Methodsmentioning
confidence: 99%
“…Here we developed models to predict the distribution of blackbrowed albatrosses foraging over the southern Patagonian shelf, part of the Patagonian large marine ecosystem and one of the most productive areas in the world (Arkhipkin et al, 2012). This area is made up of a temperate ecosystem in the north and a sub-Antarctic system in the south which is partitioned by a boundary running from south-west to north-east through the Falkland Islands (Boltovskoy, 1999).…”
Section: Introductionmentioning
confidence: 99%